GERAKAN DAKWAH MUHAMMADIYAH DI CIANJUR 1970-2012 - Wahyu Iryana; Budi Sujati; Endang Sari Wahyuni (LPPM STKIP Pangeran Dharma Kusuma Segeran Juntinyuat Indramayu, 2022)
This paper aims to find out the beginning of the emergence of Muhammadiyah, the potential of Muhammadiyah proselytizing, to the method of developing Muhammadiyah in Cianjur. Thus giving rise to a new view of the development of this civic organization. Regarding the beginning of the entry of Muhammadiyah in Cianjur Regency, which was officially formed and began to be organized in 1970. In this period Muhammadiyah established SMP and SMEA Muhammadiyah which were part of Muhammadiyah proselytizing in the field of education. The potential of Muhammadiyah proselytizing in Cianjur Regency, lies in its charitable efforts and the focus of this organization's movement is in the field of education, be it kindergarten or paud, elementary school, junior high school, high school or university startups. In the muhammadiyah development method in Cianjur Regency, it is more developed in the field of education, then, the establishment of branches that encourage the establishment of branches so that guidance on understanding the concept of Muhammadiyah is carried out in an organizational hierarchy. In addition, Muhammadiyah in Cianjur Regency penetrated into the entrepreneurial sector. This is one of the methods of developing proselytizing in reducing the poverty of people in terms of economic independence.